Impact of photo manipulation and visual literacy on consumers' responses to persuasive communication. Issue 2 (2nd April 2020) - Lazard, Allison J.; Bock, Mary A.; Mackert, Michael S.
Abstract: As digital manipulation capabilities in image-based advertising become more ubiquitous, this project investigated whether knowledge of photo manipulation techniques might alter the way audiences perceive photography-based appeals. Using an experimental design with images manipulated to communicate product effectiveness (e.g. fuller hair, longer lashes and smoother skin), we found photo manipulation is a persuasive advertising technique to positively influence consumer choices and attitudes towards brands, regardless of higher societal knowledge that digital images are easily manipulated. These findings call into question the efficacy of visual literacy skills as a defence against visual manipulation.